SUBSITUSI DEDAK PADI DENGAN POD KAKAO YANG DIFERMENTASI DENGAN Aspergillus niger TERHADAP PERFORMANS BROILER UMUR 6 MINGGU SUBSTITUTE RICE BRAN WITH FERMENTED POD COCOA WITH Aspergillus niger ON BROILER PERFORMANCE AGE 6 WEEKS Eljune R.P Habeahan1, Arm - Eljune Habaehan (Universitas Sumatera Utara, 2013)
ABSTRACT . The need for increasing animal protein consumption causes the number of rations consumption increased too. While the availability of feed ingredients such as rice bran increases, the required feed ingredient that can replace rice bran. This research aimed to determine the effect of substitution of pod cocoa husk fermented with Aspergillus niger to ration consumption, body weight gain and feed conversion racio(FCR) Broiler . The design that used in this study was completely randomized design with 6 treatments and 4 replications. Each replication consists of 5 tails Day Old Chick (DOC). The Treatments consists of R0 (Commercial Feed), R1 (the use of rice bran 12% and without fermented pod cacao), R2 (the use of rice bran 9% and fermented pod cacao 3%), R3 (the use of rice bran 6% and fermented pod cacao 6%), R4 (the use of rice bran 3% and fermented pod cacao 9%), R5 (the use of rice bran 0% and fermented pod cacao 12%).The research results showed the average ration consumption (g / head / week) 94.21; 94.40; 95.87; 93.21 and 377.69. Mean weight gain (g / head / week) 44.89; 44.84; 45.76; 46.32 and 181.80. Average conversion ratio 2.13; 2.12; 2.11; 2.03 and 8.39. The results showed that the substitution of rice bran with fruit fermented cocoa pods in the ration was not significantly different (P> 0.05) on ration consumption, but significantly different (P> 0.05) on body weight gain and the conversion ratio of broiler chickens. The conclusion of this research that substitution of rice bran with pod cocoa still be used up to 6% on broiler rations age 6 week (42 day). Keywords: Substitution, rice bran, cocoa pods, fermented, Aspergillus niger, broiler.